2014
DOI: 10.1186/1752-1947-8-34
|View full text |Cite
|
Sign up to set email alerts
|

Prucalopride reduces the number of reflux episodes and improves subjective symptoms in gastroesophageal reflux disease: a case series

Abstract: IntroductionTreatment of persistence to proton pump inhibitors or non-acid reflux episodes in patients with gastroesophageal reflux disease is challenging. Prucalopride, a selective high affinity serotonin (5-HT4) receptor agonist, might offer a possible new therapeutic alterative.Case presentationsWe report four chronically constipated female gastroesophageal reflux disease-patients with reflux symptoms and an increased number of reflux episodes in combined esophageal pH and multichannel impedance monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Compared with motilin, 5‐HT 4 agonists with good intrinsic activity and selectivity of action have greater potential to improve impaired esophageal motility, reported in a substantial number of patients with non‐obstructed dysphagia and also GERD . This possibility is supported by reports of prucalopride reducing reflux in patients with GERD (also suffering from constipation, the reason for treatment with prucalopride) and decreasing esophageal acid exposure in volunteers . However, whereas metoclopramide and prucalopride can also facilitate cholinergic activity in the human gastric antrum (consistent with an ability to increase gastric emptying), the degree of facilitation by either drug was markedly smaller than that achieved by motilin receptor activation, suggesting a weaker ability to promote gastric emptying .…”
Section: Discussionmentioning
confidence: 98%
“…Compared with motilin, 5‐HT 4 agonists with good intrinsic activity and selectivity of action have greater potential to improve impaired esophageal motility, reported in a substantial number of patients with non‐obstructed dysphagia and also GERD . This possibility is supported by reports of prucalopride reducing reflux in patients with GERD (also suffering from constipation, the reason for treatment with prucalopride) and decreasing esophageal acid exposure in volunteers . However, whereas metoclopramide and prucalopride can also facilitate cholinergic activity in the human gastric antrum (consistent with an ability to increase gastric emptying), the degree of facilitation by either drug was markedly smaller than that achieved by motilin receptor activation, suggesting a weaker ability to promote gastric emptying .…”
Section: Discussionmentioning
confidence: 98%
“…189 Although specifically designed clinical trials are lacking, some case reports suggest its efficacy in controlling GERD symptoms refractory to PPI treatment. 190 In a randomized controlled trial of typical GERD patients, no additive effect on symptom improvement was noted when domperidone was used. 191 Despite the well-known cardiac risk of domperidone, studies of real-life use reported a very limited QT effect at low daily doses.…”
Section: What Is the Role For Gastrointestinal Prokinetics In Gerd?mentioning
confidence: 99%
“…A small study showed that prucalopride can lead to improved gastric emptying and decreased esophageal acid exposure 189 . Although specifically designed clinical trials are lacking, some case reports suggest its efficacy in controlling GERD symptoms refractory to PPI treatment 190 . In a randomized controlled trial of typical GERD patients, no additive effect on symptom improvement was noted when domperidone was used 191 .…”
Section: What Is the Role For Gastrointestinal Prokinetics In Gerd?mentioning
confidence: 99%
“…32 Despite the lack of specifically designed clinical trials, some case reports suggest its efficacy in controlling GERD symptoms refractory to PPI treatment. 33 Another 5HT 4 receptor agonist from the same chemical class, revexepride (at three different doses), failed to control regurgitation in patients with GERD symptoms partially responsive to PPIs. 34 In addition, the drug was no more effective than placebo at improving reflux parameters.…”
Section: Are There Alternatives To Ppis In the Management Of Gerd?mentioning
confidence: 99%